NECROTIZING MYELOPATHY: A CASE REPORT - Barın Selçuk; Aydan Kurtaran; Elif Topçuoğlu; Murat Ersöz; Yasemin Çolak; Nilgün Şimşir; Müfit Akyüz; Hilmi Uysal (Archives of Rheumatology, 2004)
Necrotizing myelopathy, although very rare, is a neurological paraneoplastic complication of various malignancies, it may certainly be seen in non-cancer patients. It is a slowly progressing disease characterized with lower motor neuron involvement. Preservation of sensory nerve action potentials and severe denervation seen in electromyography. In this case, we present a necrotizing myelopathy case with electrophysiological findings and rehabilitation outcomes. A discussion of the case and a brief review of the literature on the subject were presented.